Shifting the instructional paradigm in higher education classrooms in Ethiopia: What happens when we use cooperative learning pedagogies more seriously?. (2020) - Tadesse, Tefera; Gillies, Robyn M.; Manathunga, Catherine
Highlights: N on-equivalent control groups design, one-way MANOVA, and SEM analyses. Formal CL does have intermediate to large effects (0.468 ≤ Cohen's d ≥ 0.717). Significant positive associations between the measured variables (.69 ≤ r ≥ .76). Higher perception was associated with formal CL than lecture-based instructions. Abstract: This study examines the relative effectiveness of formal cooperative learning (CL) compared to the traditional lecture-based instructions in improving instructional processes and learning outcomes. For this, the study used non-equivalent control groups design, collecting data from a sample of volunteered undergraduate students (n = 347) in a large public University in Ethiopia. In general, results indicate that higher perception of academic challenge, cooperative interaction, learning gains, and overall satisfaction were associated with formal CL, rather than traditional lecture-based instructions. In addition, results show that cooperative learning lessons were associated with more positive relations between academic challenge, cooperative interaction, learning gains, and overall satisfaction. Implications for higher education teaching and learning from a social interdependence theory perspective is discussed.